Parque Nacional do Monte Roraima: conflitos no uso e produção do território - Sartori, Oseias Cordeiro (2013)
With the intention to construct a reflection in respect of territorial overlaps, the present study gives priority to analysis of the conflict resulting from the creation of a total protection conservation unit in Amerindian’s territory. In this direction, bibliographic research allied with documentary analyses, interviews, questionnaires and observations, made during the field activities, provide access to necessary informations. Based on the concept of the territory as category of analysis, in case of a double presumption involving the Monte Roraima National Park and the Amerindian’s Land Raposa Serra do Sol in the state of Roraima, is utilized to support to the discussions in three principle focus. The first one points to the identification and analysis of conflicts from environmental and indigenous rights. One of the issues crucial to the arisen the tensions, including the inexistence of specific normality for the overlapping areas. In these conditions, the determinations of the environmental legislation finds resistence in the Amerindian rights. The second approach shows that the conflicts are disagreements of interests between the states and Amerindian territorialities. Even though the tensions remains stable, in virtue of the abstract ownership practiced by the National State, inclines to elevate due to manifestation of intentions of physical implementation of the National Park. The third approach concentrates the approaches in the conflicts resulting from the negotiation processes. The restrictions made the negotiations difficult partnership establishments, leading to the development of an instrument of management of conflicts able to contain different interests, permitting free practice autonomy of the subjects involved. The analysis permits the confirmation that the conflicts due to the creation of the National Park in Amerindian territory, related to the questions approaches in the theory, can be faced from the proposition of guidelines for the overlapping cases cited. This way, the interests of the Amerindians of physical reproduction and cultural can be united to the state’s interest on the Management Plan of the National Park. Such possibility can permit the establishment of negotiation process able resulting in accordance and partnership, contributing signifies to manage the conflicts in the territory studied.